2022
DOI: 10.1136/jnnp-2022-329093
|View full text |Cite
|
Sign up to set email alerts
|

Increased suicide attempt risk in people with epilepsy in the presence of concurrent psychogenic nonepileptic seizures

Abstract: ObjectivesTo test the hypothesis that people with concurrent diagnosis of epilepsy and psychogenic nonepileptic seizures (PNES) are at increased risk of attempting suicide as compared to people with epilepsy or PNES alone. To report on suicide rates.MethodsRetrospective cohort study from the UK largest tertiary mental health care provider, with linked nationwide admission and mortality data from the Hospital Episode Statistics and Office for National Statistics. Participants were 2460 people with a primary or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Inclusion criteria were a primary or secondary diagnosis of epilepsy (International Classification of Diseases, version 10 (ICD-10) code G40) or FDS (ICD-10 F44.5). We also extracted data for people with concurrent diagnosis of epilepsy and FDS, which were utilised in a previous study based on the same data[7]; however, the small sample size prevented us from investigating risk and protective factors for this group. Exclusion criteria were a primary or secondary diagnosis of psychotic disorder (ICD-10 F20-F29) or structural brain disease, including cerebral malignancy (ICD-10 C71, C79.3, D43.0-D43.2, D49.6), traumatic brain injury (ICD-10 S01, S02, S06, S07, S09), dementia or progressive neurodegenerative disease (ICD-10 F00-F03).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion criteria were a primary or secondary diagnosis of epilepsy (International Classification of Diseases, version 10 (ICD-10) code G40) or FDS (ICD-10 F44.5). We also extracted data for people with concurrent diagnosis of epilepsy and FDS, which were utilised in a previous study based on the same data[7]; however, the small sample size prevented us from investigating risk and protective factors for this group. Exclusion criteria were a primary or secondary diagnosis of psychotic disorder (ICD-10 F20-F29) or structural brain disease, including cerebral malignancy (ICD-10 C71, C79.3, D43.0-D43.2, D49.6), traumatic brain injury (ICD-10 S01, S02, S06, S07, S09), dementia or progressive neurodegenerative disease (ICD-10 F00-F03).…”
Section: Methodsmentioning
confidence: 99%
“…FDS are abrupt and observable episodes of altered behaviour or consciousness that superficially resemble epileptic seizures but are not associated with electroencephalography changes [5]. People with FDS have elevated suicide mortality rates (2.6-18.8%) as compared to the general population [6][7][8], and the presence of FDS has been found to increase the risk of suicide attempt-related hospitalisation in people with epilepsy [7].…”
Section: Introductionmentioning
confidence: 99%
“…Of all observed deaths in the observation period 1/118 (0.9%) was due to suicide in the epilepsy group and 1/38 (2.7%) in the PNES group. Suicide attempts were noted in the records of 6.1% of patients with epilepsy, 12.4% of patients with PNES and 15.6% of those with mixed seizure disorders [22]. Huepe-Artigas et al [23] determined that patients with PNES showed more suicidal behaviour and dissociative symptoms compared to patients with functional motor disorder (FMD).…”
Section: Key Pointsmentioning
confidence: 99%
“…FDS are abrupt and observable episodes of altered behaviour or consciousness that superficially resemble epileptic seizures but are not associated with electroencephalography changes 5. People with FDS have elevated suicide mortality rates (2.6–18.8%) as compared with the general population,6–8 and the presence of FDS has been found to increase the risk of suicide attempt-related hospitalisation in people with epilepsy 7…”
Section: Introductionmentioning
confidence: 99%
“… 5 People with FDS have elevated suicide mortality rates (2.6–18.8%) as compared with the general population, 6–8 and the presence of FDS has been found to increase the risk of suicide attempt-related hospitalisation in people with epilepsy. 7 …”
Section: Introductionmentioning
confidence: 99%